(untitled) (European Journal of Teaching and Education, 2022)
The Covid-19 pandemic has been going on for a while, as the virus was first discovered back in late 2019. Education is one of the most impacted sectors during the pandemic, where teachers around the world are expected to change their approaches, making sure that students are still able to learn without attending school and have ‘normal’ learning circumstances. Through this research, we investigate how teachers convey their teaching experience during the Covid-19 pandemic and how resilience appears in the teachers’ stories. Therefore the research question is how resilience appears in the teachers’ stories about their teaching experience during the Covid-19 Pandemic. The result of the study shows that all participants have reached growing phases through adversity (the Covid-19 pandemic) according to Pattterson & Kelleher’s (2005)’s four-cycle phase of resilience.